The difference Syariah learning methodology between ACIS students in UiTM Puncak Alam and Pondok school / Nurul Atirah Shaiful Rahim. - Shaiful Rahim, Nurul Atirah (2019)
With the coming of modern time signified by the globalization, the present Malaysian Higher Education Ministry had initiated various reforms to provide the Malay-Muslim society with the competent and modern educational system. Hence, to understand the learning methodology in education systems, limited studies has been conducted to examine the difference syariah learning methodology between UITM Puncak Alam and pondok schools. The objective of the research is to measuring the level of progress in learning methods both in two education systems. Second, to study how the learning system can affect thought and the way of life. And last objective is to study employment opportunities for students who are taking different learning systems. The study utilizes interview research design by interview four lecture in UITM Puncak Alam and four teachers at pondok schools. The findings of this study indicate that many difference learning methodologies between UITM and pondok schools. However, the differences can make learning methodologies more interesting and have their similarity.